Effect of home-based isometric handgrip exercise with a commercially available device on blood pressure in older adults with hypertension: A randomized controlled trial - Jirapa Champaiboon; Tanya Jitkaew; Sarissa Rangkla; Aisawan Petchlorlian (PLoS ONE, 2026)
Background Isometric handgrip exercise may help reduce blood pressure, but its effectiveness using inexpensive, home-based devices remains unclear. This study aimed to evaluate the impact of home-based isometric handgrip exercise on resting systolic blood pressure (SBP) in hypertensive older adults. Secondary outcomes included diastolic blood pressure (DBP), heart rate (HR), grip strength, safety, and satisfaction. Methods A randomized controlled trial was conducted at the Comprehensive Geriatric Clinic, King Chulalongkorn Memorial Hospital, Bangkok, Thailand. Thirty hypertensive participants aged over 60 with handgrip maximum voluntary contraction (MVC) of 10–40 kg were randomized into two groups. The intervention group (n = 15) performed isometric handgrip exercises using spring devices at 20–50% MVC. The control group (n = 15) performed non-resistive handgrip exercises. Both groups exercised 3 times/week for 8 weeks (4 sets of 2-minute holds, 1-minute rest between sets). Results The intervention group showed significant reductions in SBP (−7.33 ± 9.63 mmHg, P = 0.011) and DBP (−3.6 ± 5.79 mmHg, P = 0.03). Grip strength improved in both groups, but only SBP reduction showed a significant between-group difference (−8.19 mmHg, P = 0.03). No complications were reported, and satisfaction was high in the intervention group. Conclusion Home-based isometric handgrip exercise using commercial spring devices at 20–50% MVC significantly reduced SBP in hypertensive older adults. It is a simple, safe, and affordable exercise option, suitable for those unable to perform standard aerobic activities.